1998
DOI: 10.1183/09031936.98.11061337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formoterol, salmeterol or oxitropium bromide on airway responses to salbutamol in COPD

Abstract: We examined whether a pretreatment with formoterol, oxitropium bromide, or salmeterol might modify the dose-response curves to inhaled salbutamol in patients with stable and partially reversible chronic obstructive pulmonary disease (COPD). Sixteen outpatients with partially reversible, stable COPD received 24 microg formoterol, 50 microg salmeterol, 200 microg oxitropium bromide, or placebo on four non-consecutive days. Spirometric testing was performed immediately before inhalation of treatment and after 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…Moreover, it turned out that, even after salmeterol plus ipratropium at the conventional dose further bronchodilation was still possible with salbutamol. These results are in keeping with those of CAZZOLA et al [19] who showed that pretreatment with a conventional dose of salmeterol in COPD does not preclude the possibility of inducing further bronchodilation with salbutamol. The hypothesis that higher doses of salmeterol or ipratropium alone could have induced an improvement in airflow obstruction similar to that following the combination of salmeterol and ipratropium was not tested.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it turned out that, even after salmeterol plus ipratropium at the conventional dose further bronchodilation was still possible with salbutamol. These results are in keeping with those of CAZZOLA et al [19] who showed that pretreatment with a conventional dose of salmeterol in COPD does not preclude the possibility of inducing further bronchodilation with salbutamol. The hypothesis that higher doses of salmeterol or ipratropium alone could have induced an improvement in airflow obstruction similar to that following the combination of salmeterol and ipratropium was not tested.…”
Section: Discussionsupporting
confidence: 91%
“…We must stress that in our study [1] we did not evaluate the effects of salmeterol on airway responses to OTB, but rather the effects of OTB on airway responses to salbutamol. We agree that 200 mg OTB, which is its conventional dose, might be considered an insufficient dose.…”
Section: From the Authorsmentioning
confidence: 95%
“…With great interest, we read the article by CAZZOLA et al [1] concerning the airway responses to salmeterol in combination with another bronchodilator in patients with chronic obstructive pulmonary disease (COPD). The authors concluded that "a pretreatment with a conventional dose of oxitropium bromide (OTB) did not preclude the possibility of inducing a further bronchodilation with salbutamol in patients suffering from partially reversible COPD".…”
mentioning
confidence: 99%
“…a long-acting β 2 -agonist does not preclude the possibility of inducing a further bronchodilation with higher that the customary dose of salbutamol in patients suffering from COPD [16].…”
Section: Introductionmentioning
confidence: 99%